Effect of pretreatment on product distribution of two-step catalytic pyrolysis of spirogyra - Hussain, Z. (John Wiley and Sons Inc., 2017)
This study was aimed at investigating the effect of pretreatment on product distribution of two-step catalytic pyrolysis of spirogyra. The treatment of fresh spirogyra, putrefied spirogyra, and microbe-treated spirogyra was carried out under moist conditions. The earth burial in anaerobic conditions and microbe treatment of spirogyra were performed for biological transformation of long-chain and macromolecular compounds into hydrogen-rich and carbon-rich compounds. In later stage, two-step pyrolysis of the samples was performed to reduce the amount of water and highly oxygenated compounds, and to produce efficient liquid and gaseous fuels. Both steps of pyrolysis were catalyzed by Portland cement. However, prior to second step of pyrolysis, the pyrolysate of each sample was separated into volatile combustible liquid and a paste like organic material. The organic paste was used as feedstock for second step of pyrolysis and converted into oil and highly combustible gas. The oil product was further analyzed using GC-FID and GC-MS techniques. The experimental results revealed that the enzymatic and microbial putrefaction of spirogyra would be helpful in upgrading the fuel quality and yield of the pyrolytic conversion. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 775–780, 2017. © 2017 American Institute of Chemical Engineers Environ Prog